CUSTOMER RELATIONSHIP MANAGEMENT INFORMATION SYSTEM ST BORROMEUS HOSPITAL - Bunardi, Jimmy; Angreani, Linda Salma (MATICS, 2012)
Customer Relationship Management Information System St.Borromeus Hospitalis anapplication to process data related to the promotion, marketing and cooperation between the St.Borromeus Hospita lwith the Contractor. Data processing is not optimum cooperation with the contractorat the Marketing division of Borromeus Hospital,cause search of information about the contractor, take a bit longer so that hamper the process of promotion and marketing. Therefore it need an application that can support and solve the problem.Based on these problems the author intends arrange final by taking the title of"Customer Relationship Management Information Systems St.Borromeus Hospital ". The technique is observation data collection, interview and library research, while the phase of system development using water fall method.The author hopes that this application can assist the Marketing in the Hospital of St.Borromeusin the process ofÂ  processing and marketing campaig n to the Contractor, either from the input data, search data, scheduling agreements. The authors also hope that these applications can be made to improve the performance of the Marketing are using this application.Keyword : Customer Relationship Management, Borromeus Hospital, Marketing, Promotions